PENGUKURAN VOLUME SATUAN BAKU DAN TIDAK BAKU KELAS 6 SDEKOLAH DASAR - Juliana Margareta Sumilat; Meisara Leonita Horman (STKIP Subang, 2025)
Volume measurement is one of the fundamental competencies in elementary school mathematics, particularly for Grade 6 students. Mastery of the volume concept involves not only measuring using standard units, such as liters and cubic meters, but also non-standard units, which help students understand the concept more concretely. This literature review aims to examine previous studies on teaching strategies, student difficulties, and effective approaches in measuring volume using both standard and non-standard units. The method employed is a literature study, analyzing scientific articles, educational journals, and elementary school mathematics textbooks. The findings indicate that using concrete teaching aids, project-based learning, and measurement exercises in real-life contexts can improve students’ understanding of volume. Non-standard units play a crucial role in building initial volume concepts, while standard units prepare students for formal measurement and practical applications. This review recommends that teachers combine both types of units in the learning process and relate volume measurement to practical situations to help students internalize the concept more effectively and enjoyably.